2022
DOI: 10.3390/electronics11152287
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Using Knowledge Graph for Cybersecurity

Abstract: In today’s dynamic complex cyber environments, Cyber Threat Intelligence (CTI) and the risk of cyberattacks are both increasing. This means that organizations need to have a strong understanding of both their internal CTI and their external CTI. The potential for cybersecurity knowledge graphs is evident in their ability to aggregate and represent knowledge about cyber threats, as well as their ability to manage and reason with that knowledge. While most existing research has focused on how to create a full kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 90 publications
1
23
0
Order By: Relevance
“…In cybersecurity and cyber intelligence, the use of knowledge graphs and linked data has been prevalent due to the mostly structured nature of the recorded data related to intrusion detection systems, software vulnerabilities and malicious actors 3 , 19 . For instance, online databases like NVD 20 , CVE 21 and CWE 22 provide regular updates on software and system vulnerabilities in a structured format.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In cybersecurity and cyber intelligence, the use of knowledge graphs and linked data has been prevalent due to the mostly structured nature of the recorded data related to intrusion detection systems, software vulnerabilities and malicious actors 3 , 19 . For instance, online databases like NVD 20 , CVE 21 and CWE 22 provide regular updates on software and system vulnerabilities in a structured format.…”
Section: Related Workmentioning
confidence: 99%
“…An ad-hoc structuring of information by interlinking reports on events, i.e. a knowledge graph framework [3][4][5][6] , appears to be a viable solution. The concept of knowledge graphs has been adopted for structuring and processing of technical information on known vulnerabilities, malicious IP addresses and different relevant threats in the cyberdomain, as well as for associating other related entities such as software companies.…”
mentioning
confidence: 99%
“…Examples include the Situation and Threat Understanding by Correlating Contextual Observations (STUCCO) ontology (Iannacone et al, 2015) and the Unified Cyber Ontology (UCO) (Syed et al, 2016). Many open-source libraries also contain ontologies for the knowledge graph construction (Liu et al, 2022). Many types of graphs have been developed in the cybersecurity domain.…”
Section: Introductionmentioning
confidence: 99%
“…There also have been many graphs developed that focus on security assessments (Zhang and Liu, 2020) and network security analytics (Noel, 2018). Kurniawan et al (2022) and Liu et al (2022) identified a research need after examining reviews of previous cybersecurity knowledge-graph studies (Ding, Liu, and Zhu, 2020;Dong et al, 2020;and Yan and Liu, 2020). The identified research need consists of showing how knowledge graphs can be used to practical problems in cybersecurity at a broader scale than on a specific type of network with specific types of devices.…”
Section: Introductionmentioning
confidence: 99%
“…KG helps to systematize, handle, and use large amounts of complex knowledge in ontology-based and heterogeneous systems in cyberspace, enabling analysts to query and act on the data. Recent advantages in KG representation and modeling have been proven effective in creating, using and tackling real-world issues in cyberattacks and defense (Liu et al , 2022). Applying such advances in the cybersecurity defense domain using preexisting open-linked data resources can effectively identify hidden patterns in the offensive technique.…”
Section: Introductionmentioning
confidence: 99%